Hepatoprotection of Berberine Against Hydrogen Peroxide‐induced Apoptosis by Upregulation of Sirtuin 1. (25th May 2012) - Zhu, Xiaofei; Guo, Xiaofang; Mao, Genxiang; Gao, Zhitao; Wang, Hui; He, Qiyang; Li, Diandong
<x xml:space="preserve">Abstract</x> Berberine (BBR) has been suggested to be a hepatoprotective agent for oxidative‐stress‐related liver diseases because of its antioxidant activity. However, the antioxidant mechanisms of BBR are still not fully understood. In the present study, the protective effect of BBR was evaluated, and the underlying molecular mechanisms were investigated in hepatic cell line L02. Results from cell viability and apoptosis assay showed that in cells exposed to hydrogen peroxide (H2O2), the pretreatment of 12 μM BBR could increase cell viability by 19.10 ± 7.40% and reduce apoptotic cells by 7.91 ± 0.78%. A significant change in the expression levels of sirtuin 1 (SIRT1) and apoptosis‐related proteins was also observed in the BBR‐pretreated hepatocytes under exposure to H2O2. Furthermore, BBR exhibited a time‐dependent effect on upregulation of SIRT1 in L02 cells. This study demonstrated that the protective effect of BBR against H2O2‐induced apoptosis was associated with regulation of SIRT1 in hepatic cell line L02, which provided a possible explanation for its antioxidant activity, and implied an application of BBR for the therapeutic relevance in oxidative‐stress‐related liver diseases. Copyright © 2012 John Wiley & Sons, Ltd.